Diastereoselective Synthesis of Tetrahydroquinolines Bearing Oxindole Scaffolds via Annulation of in Situ Generated p‐Quinone Methides. Issue 13 (11th May 2020) - Wang, Junwei; Zhao, Lei; Zhao, Lin; Pan, Xiang; Lv, Cheng; Zhi, Ying; Wang, Ai; Zhao, Kun; Hu, Lihong
Abstract: A diastereoselective [4+2] annulation reaction between in situ generated p ‐quinone methides and isatin‐derived enoates has been developed. In the presence of manganese dioxide as an oxidant, a variety of tosylaminophenyl‐substituted p ‐quinone methide intermediates can be readily generated in an in situ fashion. Without pre‐preparation of p ‐QMs, this unprecedented cascade reaction proceeds efficiently under mild conditions, providing a straightforward route to synthesize 4‐phenyl‐substituted tetrahydroquinolines bearing 3, 3'‐spirooxindole scaffolds in good yields. Abstract :